Interpreting environmental change in coastal Alaska using traditional and scientific ecological knowledge - Ambrose, William G.; Clough, Lisa M.; Johnson, Jeffrey C.; Greenacre, Michael; Griffith, David C.; Carroll, Michael L.; Whiting, Alex (Frontiers in Marine Science, 2014)
Humans who interact directly with local ecosystems possess traditional ecological knowledge that enables them to detect and predict ecosystem changes. Humans who use scientific ecological methods can use species such as mollusks that lay down annual growth rings to detect past environmental variation and use statistical models to make predictions about future change. We used traditional ecological knowledge shared by local Iñupiaq, combined with growth histories of two species of mollusks, at different trophic levels, to study local change in the coastal ecosystems of Kotzebue, Alaska, an area in the Arctic without continuous scientific monitoring. For the mollusks, a combination of the Arctic Oscillation and total Arctic ice coverage, and summer air temperature and summer precipitation explained 79-80% of the interannual variability in growth of the suspension feeding Greenland cockle (Serripes groenlandicus) and the predatory whelk (Neptunea hero) respectively, indicating these mollusks seem to be impacted by local and regional environmental parameters, and should be good biomonitors for change in coastal Alaska. The change experts within the Kotzebue community were the elders and the fishers, and they observed changes in species abundance and behaviors, including benthic species, and infer that a fundamental change in the climate has taken place within the area. We conclude combining traditional and scientific ecological knowledge provides greater insight than either approach alone, and offers a powerful way to document change in an area that otherwise lacks widespread quantitative monitoring.